Experimental peritonitis in horses: peritoneal fluid composition - Mendes,L.C.N. (1999)
Sixteen adult horses were randomly divided into four equal groups of four animals and each group was injected intraperitoneally with one of the following suspension: Group I, 100×10(7) colony-forming units (CFU) of E. coli diluted in 500ml of 0.9% saline; Group II, 100×10(7) CFU of Bacteroides fragilis in 500ml of 0.9% saline; Group III, 100×10(7) CFU of E. coli in combination with 100×10(7) CFU of B. fragilis in 500ml of 0.9% saline; Group IV, 500ml of 0.9% saline. A significant increase in leukocyte number was observed in the peritoneal fluid by four hours after the inoculations in animals of Group I and II, and by eight hours in animals of Group III. The highest cell count observed was 516×10³ leukocytes/mm³. Significant increases in peritoneal fluid fibrinogen (1g/dl) and total protein (9.1%) concentrations were also observed. Horses inoculated with pure cultures of either E. coli or B. fragilis demonstrated mild and self-limiting peritonitis, while those inoculated with a combination of both bacteria demonstrated laboratory findings of higher intensity and duration.